What do children perceive as significant? - Sylvia Parker (Environmental Association of Southern Africa, 1984)
Findings from research in Zimbabwe so far suggest that many areas and items within the physical environment of township children are perceived as significant. These include natural and man-made components of streets and yards. Examples are flowers, stones, smoke, 4ogs,. cars, stores. Rubbish and waste scored low in written responses. Food, with its wide range of different items, may provide a feasible starting point for environmental education if pupil awareness is considered an advantage.